(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ever since the pandemic began, the disruption of our education systems has emerged, leading us to undergo difficult changes. Online learning is the most alternative way of learning during the pandemic. Technology allows the transmission of knowledge to be broader and more flexible. The formal online setting incorporates synchronous and asynchronous learning opportunities for language learners to interact with fellow learners actively. In this setting, students develop their language proficiency and cultural competence in the target language. An online classroom is created through a learning management system that allows students and teachers to connect synchronously or asynchronously, with the interaction between teacher and students occurring intermittently with a time delay; teacher-students are generally separated by location. This quantitative descriptive-analytical study was conducted on 50 students of Bestlink College of the Philippines through purposive sampling—a valid and reliable questionnaire collected data. With an overall weighted mean of 3.75 from General academic strand male students and a verbal interpretation of often there are advantages in online learning while the female students’ weighted mean is 3.58 and a verbal interpretation of often there are advantages in an online class. Based on the findings of the study, the following conclusions were drawn. The following recommendations were forwarded to selected Grade 12 General Academic Strand students of Bestlink College of the Philippines. Specifically, students are currently experiencing a hard time.